The economic burden of asthma prior to death: a nationwide descriptive study - Guilleminault, Laurent; Mounié, Michael; Sommet, Agnès; Camus, Claire; Didier, Alain; Reber, Laurent Lionel; Conte, Cécile; Costa, Nadège (Frontiers in Public Health, 2024)
Background: In addition to the clinical burden, asthma is responsible for a high economic burden. However, little is known about the economic burden of asthma prior to death.Objective: We performed an economic analysis to describe the costs during 12 and 24 months prior to asthma death between 2013 and 2017 in France.Methods: An observational cohort study was established using the French national health insurance database. Direct medical and non-medical costs as well as costs related to absence from the workplace were included in the analysis.Results: In total, 3,829 patients were included in the final analysis. Over 24 and 12 months prior to death, total medical costs per patient were €27,542 [26,545-28,641] and €16,815 [16,164-17,545], respectively. Total medical costs clearly increased over 24 months prior to death. Over 12 months prior to death, costs increased significantly according to age categories with mean total costs of €8,592, €15,038 and €17,845, respectively for the categories <18 years old, ]18-75[years old and [75+ years old (p<0.0001). Over 12 months prior to death, costs were statistically higher in patients with a dispensation of 6 or more SABA canisters compared to those with a dispensation of 5 or less canisters (p<0.0001). In multivariate analysis, comorbidities, hospital as location of death and dispensation of 12 or more canisters of SABA per year are independent factors of highest costs. Conclusion: To conclude, the economic burden of asthma death is high and increases with time, age, and SABA dispensation.